2010
DOI: 10.1080/19476330903353536
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant extracts from Uruguayan native plants: importance of sensory characteristics Evaluación de extractos antioxidantes de plantas nativas uruguayas: importancia de las características sensoriales

Abstract: There is increasing interest in the development of antioxidant extracts as functional ingredients. The aim of the present work was to evaluate the sensory profile, the polyphenolic (PP) content and 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging capacity of solvent extracts of three native Uruguayan plants: Achyrocline satureoides, Baccharis trimera, and Mikania guaco. Extraction solvent and native plant remarkably affected the PP content, the radical scavenging capacity, and the sensory profile of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The results are very close to those found in our work since the plants belong to the same Asteraceae family. Evaluating the total phenolic content and antioxidant capacity, it has observed that among the two native Uruguayan plants analyzed (Achyrocline satureioides and Baccharis trimera), Baccharis t. presented greater results and proved the effectiveness of the phenolic compounds found in this plant family [24].…”
Section: Extraction Optimizationmentioning
confidence: 97%
“…The results are very close to those found in our work since the plants belong to the same Asteraceae family. Evaluating the total phenolic content and antioxidant capacity, it has observed that among the two native Uruguayan plants analyzed (Achyrocline satureioides and Baccharis trimera), Baccharis t. presented greater results and proved the effectiveness of the phenolic compounds found in this plant family [24].…”
Section: Extraction Optimizationmentioning
confidence: 97%
“…Then, in a group session with the leader of the panel, the assessors agreed by consensus that the most suitable descriptors were strawberry odour and flavour, A. sellowiana odour and flavour, sweet, astringent, bitter, brown colour, aftertaste and thickness. The assessors then were trained in the evaluation of jams following the methodology proposed by Ares et al (2010). Once the panel was trained, the five samples were evaluated using unstructured 10 cm long scales anchored with 'nil/not at all' and 'high' for the different attributes.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Vargas et al (9) presented a descriptive analysis of aromatic properties of the A. satureioides extracts, obtained by CO 2 supercritical, based on the detection and description of their sensorial aspects, while Retta et al (10) evaluated and validated the A. satureioides and Helicrysum italicum extracts aromas as a potential perfume ingredient. It is also observed that the marcela extracts are used in several products marketed in the MERCOSUR region for their characteristic complex, bitter, aromatic flavor (11). Flavored compounds are widely used in the manufacture of perfume, foods, beverages, cosmetics, detergents, chemicals and pharmaceuticals, among other products (12).…”
Section: Introductionmentioning
confidence: 99%